(untitled) (Research, Society and Development, 2020)
Introduction: Transoral endoscopic thyroidectomy using the vestibular approach (TOETVA) is a safe surgical option. The potential value of this procedure is outside the cosmetic aspect and its use still persists as a gold standard, however it needs further dissemination of cases. Objective: To describe the first TOETVA performed at the Memorial São José hospital - PE. Case report: BMTM, female, 19 years old, with no previous history of radiotherapy or previous head and neck surgery, underwent thyroid ultrasound, with a nodule in the left lobe. Anatomopathological analysis was performed, detecting the absence of malignancy. In addition, ectopic parathyroid reimplantation in the left sternocleidomastoid muscle was performed. Concomitantly, the recurrent nerve -R2 and the superior laryngeal nerve-S2 were tested, with normal results. The study respected the guidelines and criteria established in Resolution 466/12 of the National Health Council (CNS). Comments: Endoscopic thyroidectomy is a favorable approach for the treatment of patients with thyroid cancer, which has a cancer nodule of 1 to 2 cm without extrathyroid extension. There are direct endoscopic (anterior or lateral cervical) and extracervical procedures to keep the thyroid exposed, but several small scars remain. However, TOETVA is an excellent choice for selected patients who need surgery for this gland, who want to avoid a scar on the neck. Conclusion: TOETVA is a safe, effective and minimally invasive treatment that provides a reduction in postoperative scar on the anterior cervical. Viable option for thyroidectomies performed with small benign lesions.